A Matter of Trust: Applying Insights From Social Psychology to Make College Affordable. (October 2016) - Goldrick-Rab, Sara; Kolbe, Tammy
The rising price of higher education threatens educational opportunity and social mobility for the most vulnerable Americans. Increasing college attendance benefits individuals and society, but efforts to reduce the price via financial aid rely primarily on economic theory: emphasizing short-term investments for long-term gains, and aiming for efficiency by targeting a narrow band of the population. Yet financial aid as currently implemented fails to effectively counter price barriers to college attainment. We argue that these failures are due, in part, to policies that were built on a narrow set of behavioral assumptions about the role of pricing in individuals' decisions to attend college. Insights from social psychology highlight decisions' relational processes and contexts. Existing policy failures have eroded public trust in financial aid as a legitimate, viable mechanism for college affordability. Cost-effective reforms that rebuild trust are a promising direction for future policy making.